Tropical forest dung beetle-mammal dung interaction networks remain similar across an environmental disturbance gradient - Chiew, LY; Hackett, TD; Brodie, JF; Teoh, SW; Burslem, DFRP; Reynolds, G; Deere, NJ; Vairappan, CS; Slade, EM (Wiley, 2022)
Conservation outcomes could be greatly enhanced if strategies addressing anthropogenic land-use change considered the impacts of these changes on entire communities as well as on individual species. Examining how species interactions change across gradients of habitat disturbance allows us to predict the cascading consequences of species extinctions and the response of ecological networks to environmental change. We conducted the first detailed study of changes in a commensalist network of mammals and dung beetles across an environmental disturbance gradient, from primary tropical forest to plantations, which varied in above-ground carbon density (ACD) and mammal communities. Mammal diversity changed only slightly across the gradient, remaining high even in oil palm plantations and fragmented forest. Dung beetle species richness, however, declined in response to lower ACD and was particularly low in plantations and the most disturbed forest sites. Three of the five network metrics (nestedness, network specialization and functionality) were significantly affected by changes in dung beetle species richness and ACD, but mammal diversity was not an important predictor of network structure. Overall, the interaction networks remained structurally and functionally similar across the gradient, only becoming simplified (i.e. with fewer dung beetle species and fewer interactions) in the most disturbed sites. We suggest that the high diversity of mammals, even in disturbed forests, combined with the generalist feeding patterns of dung beetles, confer resilience to the commensalist dung beetle-mammal networks. This study highlights the importance of protecting logged and fragmented forests to maintain interaction networks and potentially prevent extinction cascades in human-modified systems.